Online panel research : a data quality perspective - Callegaro, Mario (Chichester, West Sussex : Wiley, 2014)
Provides new insights into the accuracy and value of online panels for completing surveys Over the last decade, there has been a major global shift in survey and market research towards data collection, using samples selected from online panels. Yet despite their widespread use, remarkably little is known about the quality of the resulting data. This edited volume is one of the first attempts to carefully examine the quality of the survey data being generated by online samples. It describes some of the best empirically-based research on what has become a very important yet controversial met.
5.4 Results5.5 Discussion and conclusion; References; Part II: Nonresponse; Introduction to Part II; II.1 The nonresponse problem; II.2 The nonresponse bias; II.3 Exploring nonresponse; II.4 The chapters in Part II; References; Chapter 6: Nonresponse and attrition in a probability-based online panel for the general population; 6.1 Introduction; 6.2 Attrition in online panels versus offline panels; 6.3 The LISS panel; 6.4 Attrition modeling and results; 6.5 Comparison of attrition and nonresponse bias; 6.6 Discussion and conclusion; References
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Panel analysis; Internet research; Marketing research -- Methodology; Social sciences -- Methodology; REFERENCE -- Questions & Answers; Internet research; Marketing research -- Methodology; Panel analysis; Social sciences -- Methodology; Electronic books; Electronic books